Reliability and Minimal Detectable Change Values for Predictions of Knee Forces during Gait and Stair Ascent Derived from the FreeBody Musculoskeletal Model of the Lower Limb - Price, Phil D. B.; Gissane, Conor; Cleather, Daniel J. (Frontiers in Bioengineering and Biotechnology, 2017)
FreeBody is a musculoskeletal model of the lower limb used to calculate predictions of muscle and joint contact forces. The validation of FreeBody has been described in a number of publications however its reliability has yet to be established. The purpose of this study was therefore to establish the test-retest reliability of FreeBody in a population of healthy adults in order to add support to previous and future research using FreeBody that demonstrates differences between cohorts after an intervention. We hypothesized that test-retest estimations of knee contact forces from FreeBody would demonstrate a high intra-class correlation. Kinematic and kinetic data from nine older participants (4 men: mean age = 63±11 years; 5 women: mean age = 49±4 years) performing level walking and stair ascent was collected on consecutive days and then analysed using FreeBody. There was a good level of intra-session agreement between the waveforms for the individual trials of each activity during testing session 1 (R = 0.79-0.97). Similarly, overall there was a good inter-session agreement within subjects (R = 0.69-0.97) although some subjects showed better agreement than others. There was a high level of agreement between the group mean waveforms of the two sessions for all variables (R = 0.882-0.997). The intra-class correlation coefficients (ICC) were very high for peak tibiofemoral joint contact forces (TFJ) and hamstring forces during gait, for peak patellofemoral joint contact forces and quadriceps forces during stair ascent and for peak lateral TFJ and the proportion of TFJ accounted for by the medial compartment during both tasks (ICC = 0.86-0.96). Minimal detectable change (MDC) of the peak knee forces during gait ranged between 0.43 and 1.53 × body weight (18-170% of the mean peak values). The smallest MDCs were found for medial TFJ share (4.1 % and 5.8% for walking and stair ascent respectively, or 4.8% and 6.7% of the mean peak values). In conclusion, the results of this study support the use of FreeBody to investigate the effect of interventions on muscle and joint contact forces at the cohort level, but care should be taken if using FreeBody at the subject level.